POSS-containing polynorbornene with pendant perylene diimide: from a unique supramolecular structure to tunable luminescence properties. Issue 22 (25th May 2022) - Liu, Jie; Gao, Si-Yu; Zhang, Xin-Yi; Feng, Yakai; Wu, Han-Chun; Chen, Zhijian; Bermeshev, Maxim V.; Ren, Xiang-Kui
Abstract : The introduction of POSS cages leads to PDI-functionalized polynorbornene changing from a lamellar structure to a hexagonal columnar structure with tunable luminescence properties. Abstract : POSS-containing polynorbornene with pendant perylene diimide (PPDI-POSS) has been synthesized, with alkyl-containing polynorbornene (PPDI-C10C8) as the reference. The supermolecular structure and photoluminescence properties were elucidated using UV-Vis absorption spectra, and one- and two-dimensional X-ray diffraction. The experimental results reveal that PPDI-C10C8 possesses a lamellar structure with close PDI stacking to meet the requirement for minimum free energy. However, the introduction of POSS cages endows PPDI-POSS with a unique hexagonal columnar structure and enhanced photoluminescence properties due to the steric hindrance of POSS cages. These results may contribute to the understanding of the structure–property relationship of the optical polymers and provide some useful information for the design of polymer materials with a controllable supramolecular structure and tunable luminescence properties.